Pneumococcal LytR Protein Is Required for the Surface Attachment of Both Capsular Polysaccharide and Teichoic Acids: Essential for Pneumococcal Virulence - Ye, Weijie; Zhang, Jinghui; Shu, Zhaoche; Yin, Yibing; Zhang, Xuemei; Wu, Kaifeng (Frontiers in Microbiology, 2018)
The LytR-Cps-Psr family proteins are commonly present in Gram-positive bacteria, which have been shown to implicate in anchoring cell wall-related glycopolymers to the peptidoglycan. Here, we report the cellular function of SPD_1741 (LytR) in S. pneumoniae and its role in virulence of pneumococci. Pneumococcal ΔlytR mutants have been successfully constructed by replacing the lytR gene with erm cassette. The role of LytR in pneumococcal growth was determined by growth experiments, and surface accessibility of the LytR protein was analyzed using flow cytometry. Transmission electron microscopy (TEM) and immunoblotting were used to reveal the changes in capsular polysaccharide (CPS). Dot blot and ELISA were used to quantify the amount of teichoic acids (TAs). The contribution of LytR on bacterial virulence was assessed using in vitro phagocytosis assays and infection experiments. Compared to the wild-type strain, the lytR mutant showed a defect in growth which merely grew to a maximal OD620 of 0.2 in the liquid medium. The growth of the ΔlytR mutant could be restored by addition of recombinant ΔTM-LytR protein in culture medium in a dose-dependent manner. TEM results showed that the D39ΔlytR mutant was impaired in the surface attachment of CPS. Deletion of lytR gene also impaired the retention of TAs on the surface of pneumococci. The reduction of CPS and TAs on the pneumocccal cells were confirmed using Dot blot and ELISA assays. Compared to wild-type D39, the ΔlytR mutant was more susceptible to the phagocytosis. Animal studies showed that the ability to colonize the nasophaynx and virulence of pneumococci were affected by impairment of the lytR gene. Collectively, these results suggest that pneumococcal LytR is involved in anchoring both the CPS and TAs to cell wall, which is important for virulence of pneumococci.